Multi-period transportation network investment decision making and policy implications using econometric framework - Haque, Khademul; Mishra, Sabyasachee; Golias, Mihalis (My University, 2021)
Transportation infrastructure projects take numerous years of planning before they are scheduled for construction. Prioritization of such projects over a multi-period planning horizon (under a limited budget) is a difficult task, as it is usually formulated as a bilevel network design problem (NDP). Although multi-period network investment is studied in the literature, its application by public agencies is limited because of the complexities involved in network design problems and the computational time needed to analyze large scale networks (i.e., performing the traffic assignment at the lower level of the NDP). The contribution of this research is two-fold. First, it extends a previously published single year discrete network design formulation to a multi-period discrete network design problem (MPNDP) to capture both the spatial and temporal patterns of multi-period network investment decisions. Second, using the MPNDP investment results; and the network characteristics, this research develops and evaluates a new econometric model the Multi-Period Econometric Network Investment Model (MENIM). MENIM can be used by agencies in place of MPNDP to approximate network investments. The proposed model is calibrated and validated using medium to large scale networks and results show that it provides comparable results to MPNDP within acceptable computational times. Patterns of multi-period network investments from these numerical experiments are also extensively discussed along with policy recommendations for public agencies.
Keywords: Network design problem; Investment; Decision making; Econometric framework; Transportation planning